Archives & records management : preliminary survey report and recommendations; and, Electronic document management : survey & recommendations - Alexander-Gooding, Sharon ([CCS] [Georgetown], 2000)
Identifies key components and necessary first steps for an archives and records management project. Identifies and standardizes the key components necessary for the management of electronic records generated and received by the Secretariat.